1999
DOI: 10.1093/jjco/29.6.291
|View full text |Cite
|
Sign up to set email alerts
|

Resection-line Involvement in Gastric Cancer Patients Undergoing Curative Resections: Implications for Clinical Management

Abstract: Our data suggest, in the case of positive margins, that re-laparatomy should be considered only for patients with N0 stage disease, while patients with metastatic lymph nodes should be watched closely without the need for a more aggressive surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 7 publications
4
45
2
2
Order By: Relevance
“…The microscopic positive margin was found in 2.8% of gastric cancer patients in the present study (14.5% of all patients including non-curative cases; data not shown), which is consistent with previous studies reporting the rates from 1% to 20% [7][8][9][10][11]. Concerning the prognostic impact of surgical margin status, previous reports demonstrated that a positive margin was associated with a worse outcome [7,12,13].…”
Section: Discussionsupporting
confidence: 92%
“…The microscopic positive margin was found in 2.8% of gastric cancer patients in the present study (14.5% of all patients including non-curative cases; data not shown), which is consistent with previous studies reporting the rates from 1% to 20% [7][8][9][10][11]. Concerning the prognostic impact of surgical margin status, previous reports demonstrated that a positive margin was associated with a worse outcome [7,12,13].…”
Section: Discussionsupporting
confidence: 92%
“…Converting this continuous variable in a binary one, we find that 72 % of group A patients had a tumor larger than 4 cm in comparison with 36 % of group B patients (p \ 0.001). Similarly to the previous analysis, also for this subgroup a significantly higher incidence of tumor invasion, vascular infiltration, and lymphatic infiltration was found in group A patients (26,22, and 26 %, respectively) in comparison with group B patients (10 %, p = 0.002; 11 %, p = 0.037; and 9 %, p = 0.001, respectively). The presence of lymph node metastases was higher in patients with RM involvement than in patients with negative RMs (87 % vs 74 %, p = 0.03).…”
Section: Risk Factor Analysis For T2-t4 Lauren Diffuse/mixed Pattern supporting
confidence: 85%
“…Despite the fact that the real prognostic impact of positive RMs is still a matter of discussion, most authors [1,2,4,21,22] suggest that, in the case of R1 resection, a surgical retreatment of the patient aiming to achieve radical resection (if possible) should always be considered, in order to ensure optimal prognostic results. Lee et al [23] showed that the OS rate and the recurrence rate are not changed if R0 resection is achieved by performing additional resection for positive RMs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that microscopically positive (R1) margins after resection can be associated with worse prognosis, although the prognostic effect can differ between early-and advanced-stage gc [25][26][27][28][29][30][31] . On multivariate analysis, the predictors for a positive margin include higher T stage, higher N stage, larger tumour size, and diffuse histologic type 24,[28][29][30] .…”
Section: Summary Of Evidencementioning
confidence: 99%